A COMPARATIVE STUDY ON MATERNAL AND NEONATAL OUTCOMES IN VAGINAL BIRTH AFTER CAESAREAN SECTION VERSUS ELECTIVE LOWER SEGMENT CAESAREAN SECTION - Dr. Vartika Awasthi; Dr. Abhilasha Parihar; Dr. Charu Pandey (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: The increasing rate of caesarean sections in India has raised concern over unnecessary repeat surgeries. Vaginal Birth After Caesarean (VBAC) offers a potential alternative with fewer maternal risks and improved neonatal bonding. Materials and Methods: A prospective observational study was conducted over 18 months at our tertiary care hospital. A total of 200 women with a history of one prior lower segment caesarean section and term singleton pregnancies were enrolled. They were grouped into VBAC (n=100) and Elective Lower Segment Caesarean Section (ELSCS, n=100) based on delivery mode. Results: VBAC was successful in 78% of cases. Maternal complications such as febrile morbidity and hospital stay were significantly lower in the VBAC group. Neonatal outcomes were comparable between groups, with earlier initiation of breastfeeding observed in the VBAC group. Uterine rupture occurred in 1% of VBAC cases, with no maternal deaths. Conclusion: VBAC is a viable and safe alternative to ELSCS when proper case selection and intrapartum monitoring are ensured. Promoting VBAC in India could reduce caesarean-related morbidity and healthcare costs.